Cardiovascular Risk and Insulin Resistance in Childhood Cancer Survivors - Steinberger, Julia (2011)
OBJECTIVE: Increased cardiovascular (CV) risk has been reported in adults who are childhood cancer survivors (CCS). We sought to determine the emergence of CV risk factors in CCS while still children. STUDY DESIGN: CCS in remission ≥5 years from cancer diagnosis (n=319, age=14.5yrs), and their siblings (controls, n=208, age=13.6yrs) participated in this cross-sectional study of CV risk, which included physiologic assessment of insulin sensitivity/resistance (hyperinsulinemic euglycemic clamp). Adjusted comparisons between CCS major diagnoses (leukemia [n=110], central nervous system tumors [n=82], solid tumors [n=127]) and controls were performed using linear regression for CV risk factors and insulin sensitivity. RESULTS: Despite no significant differences in weight and body mass index, CCS had greater adiposity (waist [73.1 vs. 71.1cm, p=0.02]; percent fat [28.1vs.25.9%, p=0.007]), lower lean body mass (38.4vs.39.9 kg, p=0.01) than controls. After adjustment for adiposity, CCS had higher total cholesterol (154.7vs.148.3mg/dl, p=0.004), LDL-cholesterol (89.4vs.83.7mg/dl, p=0.002), triglycerides (91.8 vs. 84mg/dl, p=0.03) and were less insulin sensitive (M(lbm) 12.1vs.13.4mg/kg/min, p=0.002) than controls. CONCLUSIONS: CCS have greater CV risk than healthy children. Because CV risk factors track from childhood into adulthood, early development of altered body composition and decreased insulin sensitivity in CCS may contribute significantly to their risk of early CV morbidity and mortality.